Using Sociodemographic and Clinical Characteristics to Distinguish Between Drug-sensitive and Drug-resistant Tuberculosis - Yelda VAROL; Onur KARAMAN; Can BİÇMEN (Forbes Tıp Dergisi, 2023)
Objective: The purpose of this study was to investigate the significance of sociodemographic and clinical characteristics in multidrug-resistant tuberculosis (MDR-TB) and drug-sensitive tuberculosis (DS-TB) patients treated in an inpatient tuberculosis clinic. Methods: Retrospective analyzes of demographic, clinical, side effect, treatment effectiveness and mortality data were performed on MDR-TB and DS-TB patients diagnosed and treated in the chest disease and tuberculosis inpatient clinics hospitalized between 2010 and 2018. Results: There were a total of 218 tuberculosis patients, of whom 75.2% were males. When we compared the MDR-TB versus DS-TB patients, we found no statistically significant difference in terms of age, gender, marital status, and nationality (p<0.05 for all). There was a statistically significant difference in educational status between two groups (p=0.007). Also, occupational history was statistically significantly different between the MDR-TB and DS-TB population (p<0.001). MDR-TB patients had more recurrence rates than DS-TB patients (42.2-11%, respectively) and new cases were statistically significantly more in DS-TB patients (57.8-89%). The number of defeated patients was statistically higher in MDR-TB patients (p=0.045). Conclusion: In this study, we showed that patient type combined with clinical and demographic features may help to distinguish MDR-TB patients, which is a public health problem in our country.